Mengidentifikasi Perkembangan Emosional Anak Usia 5-6 Tahun pada Kelompok B di RA Muslimat NU 27 Kota Malang, Indonesia - Suryiani, Irma; Samawi, Ahmad; Putra, Yudithia Dian (Universitas Negeri Makassar, 2025)
Early childhood emotional development varies greatly and is complex from one child to another. This research was conducted at RA Muslimat NU 27 located in Malang City. This study aims to identify aspects of emotional development of children aged 5-6 years in group B at RA Muslimat NU 27 Malang City. The method used is qualitative with a descriptive approach through case studies. Data were collected through observation, interviews with teachers, and documentation. The results show that the understanding and role of the teacher is very influential in optimizing children's emotional development. Children are able to express emotions well, show confidence when performing in front of the class, and are able to manage their emotions. A positive school environment and teacher guidance are key factors in children's emotional development. This research provides insight into the importance of emotional support in early childhood